Asian Tiger Mosquito in Yucatan Peninsula: First Record of Aedes (Stegomyia) albopictus (Diptera: Culicidae) in Campeche, Mexico. Issue 6 (5th July 2020) - Hernández–Rodríguez, Jorge Luis; Perez-Pacheco, Rafael; Vásquez-López, Alfonso; Mejenes–Hernández, Meret Chantal; Granados–Echegoyen, Carlos Alejandro; Arcos-Cordova, Irma Del Rosario; Pérez–Rentería, Crescencio; Benítez-Alva, José I; Manrique-Saide, Pablo; Huerta, Herón
Abstract: This report describes the presence of Aedes albopictus Skuse (Diptera: Culicidae) in Yucatan Peninsula and represents the first record of the Asian tiger invasive mosquito in Campeche State, southeastern Mexico. We collected specimens using 11, 326 ovitraps put into houses of urban and rural areas, as part of the entomological surveillance by the local Ministry of Health from January 2019 to February 2020. We found Ae. albopictus in five of the 12 municipalities of Campeche (San Francisco de Campeche, Tenabo, Hecelchakán, Calkíni and Escárcega). We record 68 positive ovitraps and 226 Ae. albopictus larvae. This finding increases the number of mosquito species recorded in Campeche, Mexico, and possibly the potential for 22 arbovirus transmission.